1999
DOI: 10.1136/jnnp.66.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of recovery from aphasia: evidence from positron emission tomography studies

Abstract: Objectives-Language functions comprise a distributed neural system, largely lateralised to the left cerebral hemisphere. Late recovery from aphasia after a focal lesion, other than by behavioural strategies, has been attributed to one of two changes at a systems level: a laterality shift, with mirror region cortex in the contralateral cortex assuming the function(s) of the damaged region; or a partial lesion eVect, with recovery of perilesional tissue to support impaired language functions. Functional neuroima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
188
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(213 citation statements)
references
References 36 publications
(29 reference statements)
20
188
2
1
Order By: Relevance
“…In fact, many researchers have published clinical papers in support of the important role of left hemisphere (especially the peri-lesional area of the hemisphere) in the process of language functional recovery (Heiss et al, 1999;Warburton et al, 1999;Fernandez et al, 2004). On the other hand, however, other reports have also emphasized the involvement of the right hemisphere in some language functional recovery in a subgroup of post-stroke patients.…”
Section: Are the Compensatory Areas For Impaired Language Function Unmentioning
confidence: 99%
“…In fact, many researchers have published clinical papers in support of the important role of left hemisphere (especially the peri-lesional area of the hemisphere) in the process of language functional recovery (Heiss et al, 1999;Warburton et al, 1999;Fernandez et al, 2004). On the other hand, however, other reports have also emphasized the involvement of the right hemisphere in some language functional recovery in a subgroup of post-stroke patients.…”
Section: Are the Compensatory Areas For Impaired Language Function Unmentioning
confidence: 99%
“…We know that a small volume stroke can produce language defects of astonishing subtlety, suggesting that function is localizedFbut we have also discovered that recovery of adjacent tissue can recapture some of that functionFsuggesting that function may also be somewhat arbitrarily regionalized. 3 So, in the representation of brain areas vital to sexual function some specificity is to be expected and it may be possible to identify specific pathways and neurochemicals. But, recognizing the necessity for multiple and overlapping systems, there will generally be areas involved (nuclei, tracts, bodies) rather than individual neurons.…”
Section: Conceptual Framework Updatedmentioning
confidence: 99%
“…Evidence from patient data also supports this 'map extension' (Thompson, 2000a) with reports of renewed language impairments in people with aphasia with previously recovered language function, but who go on to experience a second left hemisphere stroke (Basso, Gardelli, Grassi, & Mariotti, 1989). Neuroimaging studies have also demonstrated activation of perilesional tissue adjacent to the lesioned area in response to language processing (Heiss, Kessler, Thiel, Ghaemi, & Karbe, 1999;Kurland et al, 2004;Warburton, Price, Swinburn, & Wise, 1999). Moreover, if the perilesional area surrounds an active language area it is more likely that it will be able to subsume some of language function previously carried out by the damaged regions (Marsh & Hillis, 2006) perhaps due to functional redundancy (Thompson & den Ouden, 2008).…”
Section: Stages Of Recoverymentioning
confidence: 52%
“…During this period recovery is less rapid and consists primarily of neural reorganisation leading to the formation of new alternative networks and changes in the efficacy of synaptic connections (Lazar & Antoniello, 2008). Recovery in this phase is thought to be associated with the regression of diaschisis (that is the normalisation over time of dysfunctional brain activity in areas remote or distant to the lesion and which correlate with behaviour, see Carrera and Tononi (2014) for a full review), perilesional restitution (Thompson & den Ouden, 2008;Warburton et al, 1999) or a functional transfer to the right hemisphere homologue (Saur et al, 2006). The chronic phase of recovery is dominated by neural reorganisation and compensatory cognitive strategies which may continue for a number of years (Grafman & Litvan, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation